Comparative analysis of oral descriptions of events in Swahili and Polish. A semantic and morphosyntactic perspective - Schönhof-Wilkans, Agnieszka (Lingua Posnaniensis, 2018)
The aim of this paper is to give a preferably brief overview of research undertaken in the project Comparative analysis of oral descriptions of events in Swahili and Polish. A semantic and morphosyntactic perspective funded by the Polish National Science Centre within Preludium 4 funding scheme (grant no. 2012/07/N/HS2/00963). The project includes applying the conceptual apparatus that enables comparison of genetically and typologically diverse languages within the scope of one of the most complex linguistic categories, that of diathesis. The material for analysis was collected by means of interviews with Polish and Swahili native speakers by use of audiovisual prompts. The collected material was then subjected to comparative analysis with respect to diathesis. The analysis makes use of the concepts of Jerzy Bańczerowski’s general theory of diathesis and concentrates mainly upon semantic and morpho-syntactic schemata for the diathetic meanings of transitivity and transmittivity. The semantic schemata proposed below are conceived to be universal in our theory. The lingual material reveals some morpho-syntactic schemata which are intertwined with the semantic schemata in each of the two languages under description.